Space Religionism in Kauman Settlement, Yogyakarta - Subroto, T. Yoyok Wahyu (Fakultas Teknik , UGM, 2008)
In Java's traditional city, a neighborhood called Kauman usually located at the west side of the city great mousque (Masjid Gede). At that area the clerk of the mousque together with their family live in. That is why the Kauman neighborhood - according to Indonesia's architecture literature, has been known as a moslem settlement with a strong adherent in their religious life. Many researches have been conducted which focused on this settlement, while this research focus on the experience of local people.This paper decribes the local people experience mainly in their religous aspect in Kauman. This research uses a phenomenological method based on Husserlian model. According to Husserl, the essence of things could be revealed through epoche and some steps of reduction. With this method, authors have been able to reveal a more meaning on the religious life of the people experience in their built environment. For local people of Kauman, a religious fervour (religionism) does not only present in the worship space but it coud present in their entire neighborhood. This space religionism had been created by the continous present of religious activities, atmosphere and symbols in the daily life of citizens and which are based on their culture and social history